CryoEM of Viral Ribonucleoproteins and Nucleocapsids of Single-Stranded RNA Viruses - Modrego, Andrea; Carlero, Diego; Arranz, Rocío; Martín-Benito, Jaime (Viruses, 2023)
Single-stranded RNA viruses (ssRNAv) are characterized by their biological diversity and great adaptability to different hosts; traits which make them a major threat to human health due to their potential to cause zoonotic outbreaks. A detailed understanding of the mechanisms involved in viral proliferation is essential to address the challenges posed by these pathogens. Key to these processes are ribonucleoproteins (RNPs), the genome-containing RNA-protein complexes whose function is to carry out viral transcription and replication. Structural determination of RNPs can provide crucial information on the molecular mechanisms of these processes, paving the way for the development of new, more effective strategies to control and prevent the spread of ssRNAv diseases. In this scenario, cryogenic electron microscopy (cryoEM), relying on the technical and methodological revolution it has undergone in recent years, can provide invaluable help in elucidating how these macromolecular complexes are organized, packaged within the virion, or the functional implications of these structures. In this review, we summarize some of the most prominent achievements by cryoEM in the study of RNP and nucleocapsid structures in lipid-enveloped ssRNAv.